Enhanced initiation of somatic embryos in suspension cultures of Aesculus flava and metabolic profile of zygotic embryos and somatic embryos during their development - Zdravković-Korać, Snežana; Gašić, Uroš; Jevremović, Slađana; Uzelac, Branka; Belić, Maja; Ćalić, Dušica; Milojević, Jelena (Frontiers in Plant Science, 2026)
Zygotic embryos (ZEs) of Aesculus species contain a plethora of health-promoting phytochemicals that are used in the pharmaceutical industry and traditional medicine. However, the seed yield decreases due to various stresses, and seeds often contain elevated levels of heavy metals as they are mostly collected from urban environments. Somatic embryos (SEs) could serve as an alternative source of these phytochemicals. Therefore, this study aimed to develop protocols for efficient initiation, regeneration, proliferation, and cryopreservation of A. flava SEs, while also establishing a metabolic profile of ZEs and SEs at successive developmental stages. The frequency of initiation of SEs from the filament-derived friable callus was approximately eightfold higher for explants cultured in liquid medium than on solid medium. Embryogenic suspensions with sustained proliferation and high embryogenic capacity were established and maintained efficiently by size fractionation of embryogenic cell aggregates. The selected cell lines were successfully cryopreserved by encapsulation and slow cooling, with 75% recovery from liquid nitrogen. LC/MS characterization of the ethanolic extracts revealed 117 metabolites: benzoic and cinnamic acid derivatives, flavonoids and saponins, including 58 new compounds. This analysis also provided valuable insights into dynamic alterations in specialized metabolites during embryo development. SEs in early developmental stages primarily contained flavonoids, while ZEs mainly contained saponins, whereas cotyledonary-stage SEs (CSEs) contained both flavonoids and saponins along with considerable amounts of flavan-3-ols and procyanidins. Thus, with 102/117 compounds detected, the CSEs obtained from suspension cultures may represent a promising source of metabolites for the food, pharmaceutical, and cosmetic industries. Further optimization of the protocol is required to ensure its robust applicability across A. flava clones, together with validation of metabolite yield, purity, and bioactivity.